JUMPA Vol. 4 No. 1, Feb 2017 PENGARUH KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA DENGAN KEPUASAN DAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING: PENGARUH KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA DENGAN KEPUASAN DAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING - Siswoyo Haryono Universitas Muhammadiyah Yogyakarta; Yuni Pamungkas Universitas Muhammadiyah Yogyakarta (Jurnal Manajemen dan Perbankan (JUMPA), 2017)
This thesis is the result of research on the influence of the Quality of Work Life on Performance BPS - of Statistic of D.I. Yogyakarta Province Employee with Job Statisfaction and Work Discipline as an Intervening Variable. The technique of data collection is done by distributing questionnaires to all employees of the BPS - of Statistic of D.I. Yogyakarta Province as respondents. The analysis used is descriptive and inferential analysis. Descriptive analysis is intended to provide information on the characteristics of a good research data on demographic data or data variables were obtained from the study respondents. Meanwhile, inferential analysis is intended to examine the research hypothesis by using Structural Equation Model (Structural Equation Modeling / SEM) Partial Least Square (PLS) using software Smart PLS 3. Of the 76 employees of the BPS - of Statistic of D.I. Yogyakarta Province, which could be as many as 74 respondents because there is one person who is being Task Learning and 1 more person has to move the region assignments. The results showed that there is a positive significant effect on the Quality of Work Life Job Satisfaction and Work Discipline employees. However, it turns out the effect of job satisfaction on employee performance is not significant. While the influence of the Performance Work Discipline is significantly positive. Thus Work Discipline is an intervening variable effect on the Quality of Work Life Performance, Job Satisfaction was not an intervening variable effect on the Quality of Work Life employee performance BPS - of Statistic of D.I. Yogyakarta Province.